E-learning in higher education institutions during COVID-19 pandemic: Current and future trends through bibliometric analysis - Muhammad Ashraf, Fauzi (Elsevier Ltd, 2022)
The purpose of this study is to provide a comprehensive review of e-learning in higher education institutions (HEIs) during the COVID-19 pandemic. This study presents current research issues and future progress in HEIs e-learning in the wake of the COVID-19 pandemic from 2019 to 2020 through the Web of Science (WOS) database. The analysis comprises citation analysis, co-citation analysis, and co-occurrence of keyword analysis. This bibliometric review provides essential insight for researchers to identify the most influential publications and determine the fundamental structure. Furthermore, this review facilitates future studies on the influential research trends and emerging topics. Findings present several streams of discussion based on the clusters identified from the three analyses. Subsequently, the theoretical and methodological implications on the emergence of new sub-fields and interesting future works in connection with e-learning in HEIs are presented. The outcome would aid scholars and practitioners in advancing the technology and aid towards e-learning in HEIs to ensure students' education can be sustained in the state of emergency.